2007
DOI: 10.1039/b710054j
|View full text |Cite
|
Sign up to set email alerts
|

Label-free, microfluidic separation and enrichment of human breast cancer cells by adhesion difference

Abstract: A label-free microfluidic method for separation and enrichment of human breast cancer cells is presented using cell adhesion as a physical marker. To maximize the adhesion difference between normal epithelial and cancer cells, flat or nanostructured polymer surfaces (400 nm pillars, 400 nm perpendicular, or 400 nm parallel lines) were constructed on the bottom of polydimethylsiloxane (PDMS) microfluidic channels in a parallel fashion using a UV-assisted capillary moulding technique. The adhesion of human breas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
108
0
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 141 publications
(110 citation statements)
references
References 36 publications
1
108
0
1
Order By: Relevance
“…The previous conventional macro-scale set-ups such as flow chamber [6][7][8][9] and rotating disk 10 were used to generate shear force to detach cells from the surface. Microfluidics has been also introduced into cell adhesion study [6][7][8][9][10][11][12][13][14][15][16][17][18][19] because it only requires simple setup and provides fast response. Previous microfluidic cell adhesion chip with single microchannel, 11 however, was incapable of analyzing the response of the cells simultaneously for multiple shear stresses.…”
mentioning
confidence: 99%
“…The previous conventional macro-scale set-ups such as flow chamber [6][7][8][9] and rotating disk 10 were used to generate shear force to detach cells from the surface. Microfluidics has been also introduced into cell adhesion study [6][7][8][9][10][11][12][13][14][15][16][17][18][19] because it only requires simple setup and provides fast response. Previous microfluidic cell adhesion chip with single microchannel, 11 however, was incapable of analyzing the response of the cells simultaneously for multiple shear stresses.…”
mentioning
confidence: 99%
“…In the biomedical research field, microfabrication technology has provided various tools [1] for particle separation based on electric [2][3][4], magnetic [5][6][7], optical [8], hydrodynamic [9,10], ultrasonic force [11,12], and adhesion difference [13]. Nevertheless, most attempts at efficient manipulation of bioparticles in microchannels have proven to be more challenging.…”
Section: Introductionmentioning
confidence: 99%
“…Our observation is consistent with a previous study that demonstrated that benign MCF10A breast epithelial cells can be differentiated from MCF7 breast cancer cells by their higher adhesion to label-free micro-patterned surfaces in microfluidic chips. 31 …”
Section: Microfluidic Cell Squeezer Experimentsmentioning
confidence: 99%